KEPUASAN PASIEN TERHADAP PELAYANAN RAWAT JALAN DI PUSKESMAS MARISA KABUPATEN POHUWATO - Rini Asnawati; Iskandar Simbala; Suci Kurniawaty (Universitas Muhammadiyah Gorontalo, 2020)
This research was conducted at Marisa Community health centre Pohuwato Regency. The objective of research was to determine The Description of Patients' satisfaction on outpatient's service. The design used cross sectional. The samples are 95. The research used independent statistical test. Based on the result obtained the description of patient's satisfaction about 5 dimension with direct prove value 84.2%, reliability 89.4%, responsiveness 92.6%, guarantee 94.7% and empathy 93.7. There are 5 dimension that described patient's satisfaction with not obtained the result that described not satisfied.